2022
DOI: 10.1186/s12884-022-04509-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral Dydrogesterone and 17-α hydroxyprogesterone caprate in the prevention of preterm birth

Abstract: Background Preterm birth (PTB) remains a significant problem in obstetric care. Progesterone supplements are believed to reduce the rate of preterm labor, but formulation, type of administration, and dosage varies in different studies. This study was performed to compare oral Dydrogesterone with intramuscular 17α-hydroxyprogesterone caproate (17α-OHPC) administration in prevention of PTB. Methods In this randomized clinical trial, we studied 150 wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…In case of any uncertainty regarding data integrity, several attempts were undertaken to contact authors for clarification. In case of no contact despite several attempts, studies were excluded (see Table S2 for more details on excluded trials), [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] as data trustworthiness could not be assessed for these studies. A sensitivity analysis investigating the primary outcome when including studies that were excluded based on data integrity is presented in Figure S1.…”
Section: Study Selectionmentioning
confidence: 99%
“…In case of any uncertainty regarding data integrity, several attempts were undertaken to contact authors for clarification. In case of no contact despite several attempts, studies were excluded (see Table S2 for more details on excluded trials), [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] as data trustworthiness could not be assessed for these studies. A sensitivity analysis investigating the primary outcome when including studies that were excluded based on data integrity is presented in Figure S1.…”
Section: Study Selectionmentioning
confidence: 99%
“…There are various formulations of progesterone that can be administered orally, intravaginally, or intramuscularly. A recent randomized clinical trial of 150 pregnant patients at risk of preterm birth, who had received oral Dydrogesterone (30 mg/day), 17α-hydroxyprogesterone caproate (17α-OHPC, 250 mg intramuscular, weekly), or nothing, showed that progesterone caproate obtained superior results in prolonging the latency period until birth and improving neonatal outcomes in comparison with oral progesterone and placebo [ 33 ].…”
Section: Introductionmentioning
confidence: 99%